Long-term soil nutrient and understory plant responses to post-fire rehabilitation in a lodgepole pine forest - Kaiser, Sophia; Fegel, Timothy S.; Barnard, David M.; Mahood, Adam L.; Sparks, Kya; Amundson, Kaela K.; Wilkins, Michael J.; Rhoades, Charles C. (Forest ecology and management, 2025)
Wildfires and other disturbances play a fundamental role in regenerating lodgepole pine forests. Though severe, stand-replacing fires are typical of this ecosystem, they can have dramatic impacts on soil properties and biogeochemical processes that influence the rate and composition of vegetation recovery. Organic soil amendments are often applied to manage post-fire erosion, but they can also improve soil moisture and nutrient retention and potentially alter the trajectory of post-fire revegetation. We compared change in soil nutrients, microbial communities, and understory plant cover and composition on six burned hillslopes treated with 1) biochar (20 t ha −1), 2) wood mulch (37 t ha−1), 2) biochar + mulch, and 4) an untreated control a decade after the 2010 Church’s Park fire. Wood mulch increased soil moisture and N retention the first three years following treatment. Mulch and biochar were still visible when we resampled in 2023. Mulch continued to increase soil moisture compared to unamended controls, though it had few lasting effects on soil N or cations. Conversely, biochar added alone increased dissolved organic C in soil leachate, C:N in soil and leachate, and hosted microbial communities distinct from those in mulch and combined biochar and mulch treatments. Biochar also elevated various dissolved and extractable soil N forms but reduced net nitrification. The amendments had no general effect on total graminoid, forb, or shrub cover, but had plant species-specific impacts. For example, biochar doubled cover of the dominant shrub Vaccinium scoparium, and mulch reduced cover of the most common forb (Oreochrysum parryi) by more than 50 %. The combined biochar and mulch treatment had persistent, additive effects on both soil and plant responses that exceeded impacts of the individual treatments. As seen increasingly in western North America, conifer regeneration remains scarce in the Church’s Park burn scar, and these findings suggest that mulch and biochar amendments may improve reforestation success following severe wildfires. •Biochar and woody mulch remained visible a decade after application.•Mulch had lasting effects on soil water, but little impact on soil nutrient cycling.•Biochar increased cover of the most common shrub species•Conversely, woody mulch decreased cover of the most common forb species.•There were distinct bacterial communities in biochar-amended soils.